3rd International conference on neglected and underutilized species (NUS): for a food-secure Africa. Accra, Ghana, 25-27 September 2013. Proceedings - Hall, R.A.; Rudebjer, P.G. (Bioversity International, 2016)
The '3rd international conference on neglected and underutilized species: for a food-secure Africa' was held on 25-27 September in Accra, Ghana. These proceedings include 30 papers presented at the conference, organized under the themes: 1. Resilience of agricultural and livelihood systems -- with sub-themes on agronomy, conservation, climate change, health and nutrition; 2. Upgrading value chains on NUS; 3. Creating an enabling policy environment.